Identifying the Characteristics of Engineering Innovativeness. Issue 1 (2nd January 2017) - Ferguson, Daniel M.; Jablokow, Kathryn W.; Ohland, Matthew W.; Purzer, Şenay
ABSTRACT: The use of science and engineering skills to address the novel challenges of modern society through innovative solutions is regarded as an essential strategy around the world. Many of the studies on innovators, however, are not specific to engineers. To address this gap, this study explored engineers' views of innovation and the attributes of engineers who create, develop, and implement innovations through in-depth interviews with expert engineering innovators. The study was set in an interpretivist framework and developed a socially constructed description of engineering innovativeness. Forty-five US-based expert engineering innovators were interviewed; these interviews were coded using a grounded-theory approach until categorical saturation was achieved. The results include the identification of 20 characteristics of engineering innovativeness, as well as an 'engineer's definition' of an innovation and several general descriptors of 'non-innovative' engineers. The significance of this study comes from its use of detailed qualitative data gathered from peer-recognized innovative engineers from industry, entrepreneurial ventures, and academia to identify and define characteristics of engineering innovativeness in particular. The identification of these characteristics has implications for the training and development of engineers, for engineering team formation and management, and for programs, policies, and interventions aimed at supporting innovative behavior by engineers.